Organizational Culture on Employee Performance of Aluminum Roofing Sheet Manufacturing Firms in Anambra State, Nigeria - Nnenna Dike, Goodfaith; Ifeanyichukwu Enukora, Innocent; Odira Okeke, Chidimma; Solomon Eboh, Obinna (British Journal of Marketing Studies, 2024)
The study aimed at investigating organizational culture on employee performance of aluminum roofing sheet manufacturing firms in Anambra State, Nigeria. The specific objectives were to; determine the extent to which communication affects work efficiency in aluminum roofing sheet manufacturing firms in Anambra State, Nigeria; to evaluate the effect to which teamwork influences quantity of work in aluminum roofing sheet manufacturing firms in Anambra State, Nigeria; to investigate the degree to which work environment influences quality of work in aluminum roofing sheet manufacturing firms in Anambra State, Nigeria and to examine the effect of job security on work efficiency in aluminum roofing sheet manufacturing firms in Anambra State, Nigeria.The research work was anchored on Hofstede’s cultural theory. Survey research design was adopted. The population of the study was 1781. The statistical formula devised by Borg and Gall (1973), was employed to arrive at a sample size of 342. The degree of correlation or relationships between variables were determined by the use of Analysis of Variance (ANOVA). Multiple Regression was used in testing the hypotheses. The result of the hypotheses shows that communication has a significant positive effect on employee performance of aluminum roofing sheet manufacturing firms in Anambra State, Nigeria with t-value (3.976) and p.value (0.000). Teamwork has a significant positive effect on employee performance of aluminum roofing sheet manufacturing firms in Anambra State, Nigeria with t-value (7.162) and p.value (0.005). Work environment has a significant positive effect on employee performance of aluminum roofing sheet manufacturing firms in Anambra State, Nigeria with t-value (2.840) and p.value (0.001). Job security has a significant positive effect on employee performance of aluminum roofing sheet manufacturing firms in Anambra State, Nigeria with t-value (2.579) and p.value (0.010). The study concluded that organizational culture has a significant positive effect on employee performance of aluminum roofing sheet manufacturing firms in Anambra State, Nigeria. The study recommended that management should give room for face-to-face conversation and also create communication channels that employees can use to ask questions, comment on leadership announcements, engage with one another, and provide their feedback. Management should create team work recognition program by giving them an award in front of their peer, build diverse and inclusive team, clearly define roles and responsibilities for every team member, build trust within the team and sometimes give teams autonomy in decision-making.